ANALISIS PREFERENSI WISATAWAN STAYCATION KE DAYA TARIK WISATA DI BADUNG, BALI - Vinna Lauw; I Nyoman Sudiarta; Putu Agus Wikanatha Sagita (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
Staycation is a tourism trend that is currently very popular with people of all ages, including the millennial generation as the potential age group. Almost millennial generation spend their time at Badung Regency to experience staycation. The variety of tourism products and their supporting facilities in Badung Regency will make some preferences. Therefore, this study aims to determine the characteristics and preferences of the millennial generation for tourism products while enjoying staycation in Badung Regency. The sampling technique used purposive sampling method on 100 respondents aimed to Balinese millennial generation. The data analysis technique used descriptive quantitative with cross-tabulation and chi-square test to determine the relationship between variables. The results showed that the major characteristics of millennial generation who do staycations in Badung Regency are female, living in Denpasar City, aged between 19-24 years old, unmarried status, have an undergraduate educational background, work as employe of private company, planning for a vacation, getting information via social media/ internet, doing a staycation with friends, self-organizing the trip, travelling for a night, spending less than IDR. 200,000.00 during the trip, staycation on holidays, and frequently having their staycation in Badung Regency, which is more than 5 times a year. The preferences of the millennial generation who experiencing staycation in Badung Regency are hotel-type accommodation, using motorbike, buying food and beverage at warungs, and choosing beach as their favorite tourism attractions.